The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.735427
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication for Chronic Pain Using Classic Psychedelics: A Qualitative Investigation to Inform Future Research

Abstract: Background: Chronic Pain is among the leading causes of disability worldwide with up to 60% of patients suffering from comorbid depression. Psychedelic-assisted therapy has recently been found effective in treating a host of mental health issues including depression and has historically been found to be useful in treating pain. Reports of self-medication for chronic pain using psychedelic drugs have been widely documented, with anecdotal evidence indicating widespread success in a range of pathologies.Aims: In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 108 publications
(137 reference statements)
1
34
0
Order By: Relevance
“…Psychedelics modulate the immune system via 5-HT1, 5-HT2, and sigma-1 receptor activity (18, 233, 241-248). Altered immune system function, mainly characterized by chronic lowgrade inflammation is associated with a range of psychiatric disorders (57,(249)(250)(251) and it remains an open question whether the potential anti-inflammatory activity of psychedelics will play a role in autoimmune disorders (252) or chronic pain (253,254).…”
Section: Arousalmentioning
confidence: 99%
“…Psychedelics modulate the immune system via 5-HT1, 5-HT2, and sigma-1 receptor activity (18, 233, 241-248). Altered immune system function, mainly characterized by chronic lowgrade inflammation is associated with a range of psychiatric disorders (57,(249)(250)(251) and it remains an open question whether the potential anti-inflammatory activity of psychedelics will play a role in autoimmune disorders (252) or chronic pain (253,254).…”
Section: Arousalmentioning
confidence: 99%
“…Recent studies found that psychedelic-assisted therapy can effectively treat pain and mental health disorders [ 6 ]. Various reports of self-medication using psychedelics are documented, with anecdotal evidence of practical successes [ 7 ]. Suppose we consider our current pain medication regime, including non-steroidal anti-inflammatory drugs (NSAIDs), weak opioids, anti-depressants, and anticonvulsants.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose we consider our current pain medication regime, including non-steroidal anti-inflammatory drugs (NSAIDs), weak opioids, anti-depressants, and anticonvulsants. Most pain medication regime has various side effects if used for an extended period; for example, opioid use is linked chiefly with drug dependence and has contributed to the ongoing international opioid crisis [ 7 ]. Hence there are several problems with current treatments for pain management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations